Protocol for a scoping review on 'surgical sabermetrics:' technology-enhanced measurement of operative non-technical skills. Issue 2 (3rd February 2023) - Howie, Emma; Wigmore, Stephen J; Daglius Dias, Roger; Skipworth, Richard; Yule, Steven
Abstract : Introduction: Surgeons need high fidelity, high quality, objective, non-judgemental and quantitative feedback to measure their performance in order to optimise their performance and improve patient safety. This can be provided through surgical sabermetrics, defined as 'advanced analytics of digitally recorded surgical training and operative procedures to enhance insight, support professional development and optimise clinical and safety outcomes'. The aim of this scoping review is to investigate the assessment of surgeon's non-technical skills using sabermetrics principles, focusing on digital, automated measurements that do not require a human observer. Methods and analysis: To investigate the current methods of digital, automated measurements of surgeons' non-technical skills, a systematic scoping review will be conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines, using databases from medicine and other fields. Covidence software is used for screening of potential studies. A data extraction tool will be developed specifically for this study to evaluate the methods of measurement. Quality assurance will be assessed using Quality Assessment Tool for Diverse Designs. Multiple reviewers will be responsible for screening of studies and data extraction. Ethics and dissemination: This is a review study, not using primary data, and therefore, ethical approval is not required. A range of methods will be employed for dissemination of the results of this study, including publication in journals and conference presentations.